Analysis of Low Inductance Design for Laminated Busbar - LIU Yuzhu; WANG Liang; HE Xiaogang; SUN Shilin (Kongzhi Yu Xinxi Jishu)
It compared the structures of laminated busbar which commonly used in converter module. With theoretic analysis and simulation comparison, the design basis of laminated busbar was obtained and several conventional methods for reducing the inductance of laminated busbar were presented, which could provide reference for the design of module structure and the production of laminated busbar.